Metastasis of Breast Lobular Carcinoma to Endometrium Presenting as Recurrent Abnormal Uterine Bleeding: A Case Report and Review of Literature - Rodolfo Franco-Márquez; Adrián Gerardo Torres-Gaytán; Marcela Anahí Narro-Martinez; Anahí Carrasco-Chapa; Benjamín Gómez Núñez; Estefanía Boland-Rodriguez (Hindawi Limited, 2019)
There are few reports of breast cancer cases with uterine metastases. Here, we report a metastatic lobular carcinoma to endometrium presenting as abnormal uterine bleeding. Diagnosis was based in previous lobular breast carcinoma and immunohistochemistry.